Pengaruh Ukuran Perusahaan, Pertumbuhan Penjualan Dan Profitabilitas Terhadap Nilai Perusahaan (Studi Empiris Pada Perusahaan Manufaktur Subsektor Industri Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Periode 2020-2024) - Yarna Laowo; Ria Rosalia Simangunsong (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2026)
Abstract. This study aims to find out the effect of Company Size, Sales Growth, and Profitability on Company Value, both partially and simultaneously, in manufacturing companies in the food and beverage industry sub-sector listed on the Indonesia Stock Exchange for the period 2020-2024. The approach used is a quantitative approach with a causal associative research type. Secondary data in the form of financial reports were obtained through purposive sampling with certain criteria, resulting in 13 companies with a total of 65 observations. The data analysis method uses multiple linear regression analysis with Eviews 12 software, and the selected model is Panel EGLS (Cross-section Random effects). The results show that Company Size has a positive and significant effect on Company Value with a regression coefficient of 1.013. Sales Growth does not have a significant effect on Company Value with a regression coefficient of -0.310. Profitability has a positive and significant effect on Company Value with a regression coefficient of 5.346 and is the most dominant variable. Simultaneously, Company Size, Sales Growth, and Profitability have a significant effect on Company Value with an adjusted R2 value of 84.74%. The implication of this study is that company management should prioritize increasing profitability and conducting measured asset expansion to increase company value